Enrichment pattern of leachable trace metals in roadside soils of Miri City, Eastern Malaysia - Ramasamy, Nagarajan; Jonathan, M.; Roy, P.; Prasanna, Mohan Viswanathan; Aruchunan, Elayaraja (Springer, 2014)
This article presents the results on distribution and enrichment pattern of acid-leachable trace metals (ALTMs) from roadside soil of Miri city, Sarawak, East Malaysia. The city is one of the fastest developing in the Malaysian region with huge petroleum resources. ALTMs Fe, Mn, Cr, Cu, Ni, Co, Pb, Zn and Cd along with organic carbon and carbonates (CaCO3) were analyzed in 37 soil sediments collected from roadside. The enrichment of ALTMs [especially Cu (0.4-13.1 µg g-1), Zn (9.3-70.7 µg g-1), Pb (13.8-99.1 µg g-1)] in the roadside soils indicate that these metals are mainly derived from sources related to traffic exhausts, forest fires and oil refineries. The comparative study and enrichment pattern of elements indicates that Mn, Cu, Zn and Pb are enriched multi-fold than the unpolluted soil and Ni, Pb, Cd in some samples compared to Sediment Quality Guidelines like Lowest Effect Level (LEL) and Effects Range Low (ERL) in the region which is mainly due to the recent industrial developments in the region. © 2014 Springer-Verlag Berlin Heidelberg.